THE EFFECT OF ACCOUNTABILITY, COMPETENCY, PROFESSIONALISM, INTEGRITY AND OBJECTIVITY OF PUBLIC ACCOUNTING ON AUDIT QUALITY WITH INDEPENDENCE AS MODERATING VARIABLES (Empirical Studies in Medan City Public Accountant Firm) - Lubis, Adi Sahputra (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to examine and analyze the effect of accountability, competency, professionalism, integrity and objectivity on audit quality with independence as a moderating variable in public accounting firms in Medan City. This type of research is an associative research with a quantitative approach. The population of this research is the Public Accounting Firm located in Medan City. The sample selection method uses a census (saturated sample), the number of samples used is 120 sample data. The collection of data used in this study is primary data with steamy questionnaire. Data analysis techniques used descriptive statistics and SEM-Partial Least Square (PLS), which were processed using the SmartPLS 3.0 program. The results showed that professionalism and integrity had a positive effect on audit quality, while accountability, competency and objectivity had a negative effect on audit quality. Independence as a moderating variable weakens the effect of accountability, competency, and professionalism on audit quality, while independence as a moderating variable strengthens the effect of integrity, and objectivity on audit quality. The independence variable in this study cannot moderate the relationship between accountability, competency, professionalism, integrity, and objectivity with audit quality at the Public Accountant Office in Medan. Among the five variables, professionalism has the greatest effect on Audit Quality.